Anterior uterocervical angle on ultrasound in singleton pregnancies - a predictor of spontaneous pre-term birth - Bhargavi Patel; Harneet Narula; Amit Jain; Aditi Vohra (Asian Journal of Medical Sciences, 2025)
Background: The success of labor induction is strongly influenced by the condition of the cervix. The uterocervical angle (UCA), found where the cervical canal meets the lower uterine segment has recently emerged as a promising ultrasound indicator for predicting pre-term birth (PTB).